IN VITRO EVALUATION OF SESUVIUM SESUVIOIDES (FENZL) VERDC. (AIZOACEAE) OF CHOLISTAN DESERT FOR ANTI-OXIDANT, ANTIMICROBIAL AND CYTOTOXIC POTENTIAL - Maria Pervaiz; Sabira Sultana; Naheed Akhtar; Aisha Sethi; Muhammad Khawar Abbas; Rida Siddique; Faheem Hadi; Rimsha Khan; Abdul Wadood Chishti (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The aim of current study was to explore the antioxidant, antimicrobial and cytotoxic potential of different extracts (Sesuvium sesuvioides ethanol (SS E), Sesuvium sesuvioides n-hexane (SS nh, Sesuvium sesuvioides distilled water (SS DW). Antioxidant activity of extracts of selected plant were determined by using 2, 2-diphenyl-1-picrylhydrazyl radical scavenging assay as designated by researchers. Folin-Ciocaletu reagent method was used to determine total phenolic contents (TPC). The total flavonoid content (TFC) of the extracts were determined by aluminum chloride complex forming assay. The agar well diffusion method was used, against gram positive and negative bacterial strains. The hemolytic activity was determined by Spectro-photometric method for different extracts against red blood cells and PBS were be used as negative control and Triton-X-100 as positive control. The Sesuvium sesuvioides ethanol extract showed maximum antioxidant (radical scavenging) effects 66.667% with IC50 value (81.48±1.22) μg/mL which was significant (P<0.01). Maximum effect of TPC (mg GAE/g) was exhibited by n-hexane extract 172.4±1.22 mg GAE/g. Similarly, the n-hexane extract showed maximum TFC activity 21.428±2.02mg QE/g. Among three extracts of Sesuvium sesuvioides, maximum zone of inhibition against E. coli and B. subtilis was shown by distilled water extract [(18±0.333) mm], [(19±0.577) mm] respectively. n-hexane extract showed higher hemolytic activity than other extracts (32.525%). Thus, results of study showed that extract of Sesuvium sesuvioides exhibit antimicrobial, cytotoxic and antioxidant potential.